Interactive Regimes of Reduced Irrigation and Salt Stress Depressed Tomato Water Use Efficiency at Leaf and Plant Scales by Affecting Leaf Physiology and Stem Sap Flow - Yang, Hui; Shukla, Manoj K.; Mao, Xiaomin; Kang, Shaozhong; Du, Taisheng (Frontiers in Plant Science, 2019)
Interactive effects of reduced irrigation and salt stress on leaf physiological parameters, biomass accumulation, and water use efficiency (WUE) of tomato plants at leaf and whole plant scales were investigated in a field experiment during 2016 and a greenhouse experiment during 2017. Experiment utilized two irrigation regimes (full, 2/3 of full irrigation) and four soil salt regimes (0, 0.3%, 0.6%, 0.9% in 2016 season; and 0, 0.2%, 0.3%, 0.4% in 2017 season). Three salts, sodium chloride, magnesium sulfate, and calcium sulfate (mass ratio of 2:2:1), were homogeneously mixed with soil prior to packing into containers (0.024 m3). Li-COR 6400 was used to measure tomato leaf physiological parameters. Instantaneous and intrinsic water use efficiency were determined at leaf scale, yield water use efficiency, and dry biomass water use efficiency were determined at whole plant scale. Plants irrigated with 2/3 of full irrigation with zero soil-salt treatment had higher dry biomass and yield per plant, resulting in the highest WUEDM and WUEY at whole plant scale. Increasing soil salinity decreased dry biomass and yield, leading to greater decreases in whole plant WUEDM and WUEY under both irrigation treatments. At full irrigation, no decreases in stomatal conductance and slight increase in Pn led to higher WUEint at leaf scale during both years. Under full and reduced irrigation, increasing soil salt content decreased Pn and Tr and led to reductions in WUEins at the leaf scale. However, compared to full irrigation, reduced irrigation improved WUEins with a significant decline in Tr in no salt and 0.3% soil-salt treatments during both years. For soil salt content of 0.6%, stomatal limitation due to salt stress resulted in higher WUEint, but soil salt content of 0.9% decreased WUEint due to non-stomatal limitation. Soil salt content significantly decreased sap flow, with the maximum variation of daily sap flow per plant of 7.96–31.37 g/h in 2016 and 12.52–36.02 g/h in 2017. Sap flow rate was linearly related to air temperature, solar radiation, and vapor pressure deficit. These results advance knowledge on tomato response to abiotic stresses and could improve management of tomato production in water- and salt-stressed areas.